2008
DOI: 10.1177/1934578x0800301227
|View full text |Cite
|
Sign up to set email alerts
|

Olive-oil Phenolics and Health: Potential Biological Properties

Abstract: Extra virgin olive oil, the primary source of oil in the Mediterranean diet, differs significantly in composition from dietary lipids that are consumed by other populations. The several minor constituents of virgin olive oil include vitamins such as alphaand gamma-tocopherols (around 200 ppm) and beta-carotene, phytosterols, pigments, terpenic acids, flavonoids, squalene, and a number of phenolic compounds, such as hydroxytyrosol, usually grouped under the rubric "polyphenols". The antioxidant and enzyme-modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Extensive research highlighted the importance of EVOO polyphenols in limiting NO production in immune system cells, treated with LPS to simulate inflammatory conditions. HT above all [67,104,140] but also oleuropein [67,108] and complex EVOO polyphenols extracts [107,127] were able to impede NO overproduction in monocytes and macrophages. These effects occurred actually not only in these cell types, but also in almost all the tissues studied, both in vitro [129,141] and in vivo [98,142].…”
Section: Inos Modulationmentioning
confidence: 89%
See 1 more Smart Citation
“…Extensive research highlighted the importance of EVOO polyphenols in limiting NO production in immune system cells, treated with LPS to simulate inflammatory conditions. HT above all [67,104,140] but also oleuropein [67,108] and complex EVOO polyphenols extracts [107,127] were able to impede NO overproduction in monocytes and macrophages. These effects occurred actually not only in these cell types, but also in almost all the tissues studied, both in vitro [129,141] and in vivo [98,142].…”
Section: Inos Modulationmentioning
confidence: 89%
“…In vitro, EVOO extracts or simple phenols demonstrated, particularly in monocytes and activated macrophages, the ability to inhibit MAPKs activation, which in turn caused inhibition of phosphorylated-IκBα and thus NF-κB expression and translocation into the nucleus. These effects have been noticed in particular in those cells treated with oleuropein aglycone [105], Tyr [98,106], and HT [104], as well as complex phenolic extracts [107,108]. At the intestinal level, the breakdown of the NF-κB inhibitor IkBα was counteracted by EVOO phenolic extracts or by simple phenols HT and Tyr glucuronide and sulfates in intestinal Caco-2 cells, where NF-κB was experimentally activated by a mixture of dietary oxysterols [99] or by LPS [88].…”
Section: Modulatory Function Of Evoo Polyphenols On Nf-κb Expression mentioning
confidence: 98%
“…Subjects did not modify their diet, with the exception of the consumption of the study oil, so that food intake (apart from added fat replace) before and during the test period was the same. Since most of the recent studies have highlighted a strong correlation between the beneficial properties of EVOO and its phenolic concentration 3, 4, 7, 10, 16, 20, in this research we selected an oil rich in phenolic compounds, with high amounts of secoiridoids, mainly oleuropein derivatives (Table 2). It has been recently pointed out the capacity of 3,4‐DHPE‐EA to prevent amyloid aggregation of human amylin, a hallmark of Type II diabetes 29.…”
Section: Resultsmentioning
confidence: 99%
“…Olive oil consumption has shown to reduce oxidative damage and cardiovascular risk in European populations 1, 2. Some authors report to have found increased HDL cholesterol 3–5, increased antioxidant capacity 6–8, and gene expression from antioxidant enzymes 6, 9 in intervention periods with participants consuming daily EVOO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation